2023
DOI: 10.23923/rpye2023.01.233
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones y Tablets, desarrollo psicológico y aprendizaje infantil: una revisión sistemática

Abstract: Background: This systematic review examines the current evidence on the use of smartphones and tablets (SP&T) in children, as growing interest has been generated to verify its impact on different aspects of psychological development and learning. Method: a search of articles was carried out in the EBSCO, Pubmed, Science Direct, Scopus, and Web of Science databases. A sample of 42 articles that met the inclusion and exclusion criteria was selected. Content analysis was performed, extracting information on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Por otro lado, Franz-Torres et al 11 , señala que el uso de smartphones y tabletas en niños está asociado con el desarrollo de habilidades cognitivas clave y habilidades socioemocionales. Además, los estudios realizados por Ubhi H et al 12 , y Yang J et al 13 , han demostrado que ciertas aplicaciones, como la App SF28 (SmokeFree28) y la App Pain Guard, pueden ser efectivas en el abordaje del tabaquismo y el manejo del dolor en pacientes con cáncer, respectivamente.…”
Section: Discussionunclassified
“…Por otro lado, Franz-Torres et al 11 , señala que el uso de smartphones y tabletas en niños está asociado con el desarrollo de habilidades cognitivas clave y habilidades socioemocionales. Además, los estudios realizados por Ubhi H et al 12 , y Yang J et al 13 , han demostrado que ciertas aplicaciones, como la App SF28 (SmokeFree28) y la App Pain Guard, pueden ser efectivas en el abordaje del tabaquismo y el manejo del dolor en pacientes con cáncer, respectivamente.…”
Section: Discussionunclassified
“…Therefore, early childhood screen use and its possible association with developmental disorders, the prevalence of which is increasing, should be addressed in consultations. (16) Several studies have shown that smartphone and tablet use is associated with increased susceptibility to obesity, poorer sleep quality, depressive symptoms, attention deficit hyperactivity disorder, and behavioral and prosocial problems. Other studies have looked at the positive effects of opportunities for social communication, creativity, expression and fun in the family or the way they maintain friendships and spend their leisure time, thanks to the difference in connection between girls and boys at the socioeconomic level, opportunities for learning, education and development are available from remote areas.…”
Section: Introductionmentioning
confidence: 99%